Narrative Cross Boundary in Qur'anic Narrations - Maryam Bakhshi (آموزه‌های قرآنی, 2019)
Narrative cross boundary is a term in which the boundary between narrative and reality is broken, it has four varieties: 1- writer’s cross boundary, 2- addressing, 3- ontological, and 4- rhetoric. Which can be ascending or descending. The use of this arrangement is more common in the postmodern era and is considered as a tool of contemporary critical discourse. The great art of the Qur'an in the field of narration is the same as breaking the boundary between the narrative and the outside world, which in addition to the four mentioned ones includes the other two types of linguistic cross boundary and narrative non-boundary which are specific to this text. Bounding in the Quran has not been influenced by humor or comedy; rather, it has a wondrous functioning and contains valuable and eternal goals. And unlike the human narrative that has an anti-realistic and form aspect function, cross boundary actually takes place and has a form and content aspect. The present paper Based on the descriptive-analytical method, examines the types of narrative bounding in the stories of the Holy Quran and seeks to prove that the Quran goes beyond classical literary schools, realism, modernism, and postmodernism. And it respond the question, “Is cross-boundary as a way of breaking the boundary between fiction and reality, denying that the Quranic stories are real?”